2018
DOI: 10.1021/acs.jpcc.8b07729
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Dehydrogenation of Methane Enhanced by μ2-Oxo Ligands in Tantalum Cluster Cations [TaxO]+, x = 4, 5

Abstract: The gas-phase reactions of [Ta x O y ]+ (x = 4, 5; y = 0, 1) nanoclusters with methane have been explored in a ring-electrode ion trap under multicollision conditions and theoretically with the use of first-principles quantum simulations. At room temperature, Ta4 + dehydrogenates consecutively two methane molecules with the concurrent elimination of H2, whereas Ta5 + is found to be unreactive. Both of the corresponding mono-oxides, [Ta4O]+ and [Ta5O]+, demonstrate significantly increased reaction rates. Bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
42
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 52 publications
(80 reference statements)
10
42
1
5
Order By: Relevance
“…Among the pertinent results from recent investigations on this topic (i.e.Ta 4 + ), [8] we note: (i) The reaction of Ta 4 + with methane starts with the formation of [4Ta,C,2H] + (here and in the following we denote the species determined through the mass‐spectrometric experiments in a form that gives only the material's stoichiometry), followed by a facile second dehydrogenation reaction. (ii) First‐principles density functional theory (DFT) calculations predicted that in the first step of the reaction, a H 2 Ta 4 C + carbide dihydride structure is energetically favored over carbene (Ta 4 CH 2 + ) [8] . To the best of our knowledge, prior to that study [8] only carbenes (‐CH 2 ) and carbyne hydrides (‐H and ‐CH) have been identified as primary reaction products.…”
Section: Figurementioning
confidence: 99%
“…Among the pertinent results from recent investigations on this topic (i.e.Ta 4 + ), [8] we note: (i) The reaction of Ta 4 + with methane starts with the formation of [4Ta,C,2H] + (here and in the following we denote the species determined through the mass‐spectrometric experiments in a form that gives only the material's stoichiometry), followed by a facile second dehydrogenation reaction. (ii) First‐principles density functional theory (DFT) calculations predicted that in the first step of the reaction, a H 2 Ta 4 C + carbide dihydride structure is energetically favored over carbene (Ta 4 CH 2 + ) [8] . To the best of our knowledge, prior to that study [8] only carbenes (‐CH 2 ) and carbyne hydrides (‐H and ‐CH) have been identified as primary reaction products.…”
Section: Figurementioning
confidence: 99%
“…Betreffend die einschlägigen Resultaten neuerer Untersuchungen über dieses Thema (d. h. Ta 4 + ), [8] so stellen wir fest: (i) Der Beginn der Reaktion von Ta 4 + mit Methan findet über die Bildung von [4Ta,C,2H] + (hier und in weiterer Folge bezeichnen wir die Spezies aus massenspektrometrischen Experimenten so, dass nur die Stöchiometrie der Verbindung wiedergeben wird) statt, gefolgt von einem zweiten Dehydrierungsschritt. (ii) Auf dem Grundbegriff basierende Berechnungen mittels Dichtefunktionaltheorie (DFT) sagten voraus, dass im ersten Reaktionsschritt eine H 2 Ta 4 C + Carbid‐Dihydridstruktur energetisch gegenüber der eines Carbens (Ta 4 CH 2 + ) bevorzugt ist [8] . Nach unserem besten Wissen sind vor dieser Studie [8] lediglich Carbene (‐CH 2 ) und Carbin‐Hydride (‐H und ‐CH) als primäre Reaktionsprodukte identifiziert worden.…”
Section: Figureunclassified
“…(ii) Auf dem Grundbegriff basierende Berechnungen mittels Dichtefunktionaltheorie (DFT) sagten voraus, dass im ersten Reaktionsschritt eine H 2 Ta 4 C + Carbid‐Dihydridstruktur energetisch gegenüber der eines Carbens (Ta 4 CH 2 + ) bevorzugt ist [8] . Nach unserem besten Wissen sind vor dieser Studie [8] lediglich Carbene (‐CH 2 ) und Carbin‐Hydride (‐H und ‐CH) als primäre Reaktionsprodukte identifiziert worden. So konnte beispielsweise mittels Infrarot Multipler‐Photonendissoziationsspektroskopie (IRMPD) gezeigt werden, dass die Methandehydrierung, welche von kationischen Übergangsmetallatomen vermittelt wird, üblicherweise mit der Bildung von Carbenstrukturen einhergeht, einschließlich von TaCH 2 + für das Ta + Ion [9] .…”
Section: Figureunclassified
See 2 more Smart Citations